Spring-loaded reproduction : effects of body condition and population size on fertility in migratory caribou (Rangifer tarandus) - Pachkowski, Mélanie Dawn; Côté, Steeve D.; Festa-Bianchet, Marco (Canadian Journal of Zoology, 2020)
In many ungulates, female fecundity is affected by body condition and has important effects on population dynamics.In some species, females adopt a conservative strategy, reducing reproductive effort when population density is high. Weinvestigated what factors affect the probability of gestation in adult female caribou (Rangifer tarandus(L., 1758)) from theRivière-George herd in northern Quebec and Labrador over 5 years that spanned various population sizes and trends. Similar toother populations of migratory caribou, the probability that a female was pregnant in spring increased with body mass andpercent body fat. The probability of gestation appeared to be reduced by high infestation of warbles (Hypoderma tarandi(L., 1758)).The proportion of females pregnant varied between years and was lower at high population size. Females of similar mass,however, were pregnant regardless of whether the population was increasing at low density, had reached a peak, or wasdeclining. Compared with other ungulates that reduce maternal expenditure at high density, female caribou of the Rivière-George herd may have a risk-prone reproductive strategy Chez de nombreux ongulés, la condition corporelle a une incidence sur la fécondité des femelles qui, elle, a des effets importants sur la dynamique des populations. Les femelles de certaines espèces adoptent notamment une stratégie conservatrice consistant à réduire leur effort de reproduction quand la densité de la population est élevée. Nous avons examiné les facteurs qui influent sur la probabilité de gestation des caribous (Rangifer tarandus(L., 1758)) femelles adultes du troupeau de Rivière-George, dans le nord du Québec et au Labrador, sur une période de 5 ans couvrant diverses tailles et tendances de population. À l’instar d’autres populations de caribous migrateurs, plus la masse corporelle et le pourcentage de graisse corporelle étaient élevés, plus la probabilité qu’une femelle soit en gestation au printemps était grande. Un degré élevé d’infestation d’hypodermes (Hypoderma ...